1995
DOI: 10.1021/ma00124a031
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Homopolyimides and Copolyimides Derived from 3,3',4,4'-Biphenyltetracarboxylic Dianhydride/1,3-Bis(4-aminophenoxy)benzene/1,12-Dodecanediamine. 1. Materials, Preparation, and Characterization

Abstract: Crystalline homopolyimides are shown to occur by DSC from 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) and either 1,3-bis(4-aminophenoxy)benzene (134APB) or 1,12-dodecanediamine (C12). Additionally, copolyimides synthesized from these monomers are crystalline in all compositions studied. Each composition was found to have a singular glass transition temperature, which is rectilinearly dependent on the percent of 134APB/C12. A similar relationship is found for the crystallization temperature but not for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 2 publications
7
42
0
Order By: Relevance
“…An approach such as the incorporation of a flexible ether linkage and meta oriented phenylene rings into the polymer backbone has led to an increase in polymer chain flexibility and solubility of neat polyimides, but at the same time has lowered the effective upper use temperature of these polymers. [3][4][5][6][7][8][9] This drawback makes them rather unqualified for the ever increasing demand for higher upper use temperature materials for microelectronics applications. Similarly, incorporation of inorganic clay leads to high thermal stability, but at the expense of fracture toughness and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…An approach such as the incorporation of a flexible ether linkage and meta oriented phenylene rings into the polymer backbone has led to an increase in polymer chain flexibility and solubility of neat polyimides, but at the same time has lowered the effective upper use temperature of these polymers. [3][4][5][6][7][8][9] This drawback makes them rather unqualified for the ever increasing demand for higher upper use temperature materials for microelectronics applications. Similarly, incorporation of inorganic clay leads to high thermal stability, but at the expense of fracture toughness and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that the multiple melting endotherms were probably not due to the melting of different crystal forms. It is also worth noting that, multiple melting endotherms in the DSC scans of isothermally annealed homopolyimide BPDA/TPER have already been reported, and Hsiao et al considered the phenomenon resulted from the recrystallization/reorganization process during heating [31,33,34]. The lowest endothermic peak in every DSC curves of Fig.…”
Section: Crystallization Of Piss With Crystalline Polyimide Hard Blockmentioning
confidence: 87%
“…The lowest endothermic peak in every DSC curves of Fig. 2 could be attributed to the annealing process since it always occurs at approximately 10 C above the annealing temperature [31,34]. It was found that the fusion heat of the lowest endothermic peak also exhibited a decrease trend at high temperature as the diffraction intensity (Since in some DSC curves, the lowest endothermic peak overlapped with near peak, the fusion heats of the lowest endothermic peaks were not given).…”
Section: Crystallization Of Piss With Crystalline Polyimide Hard Blockmentioning
confidence: 96%
“…In recent years, some types of PIs were proven to be biocompatible [4], and they have been used in biomedical fields as flexible and implantable intracortical electrode arrays [5] and as microstructured substrates for contact guidance of cell growth [6], on condition of being patterned at micro or nanoscale. However, the strong intermolecular forces between the aromatic PI chains make them difficult to process because they decompose prior to melting and are insoluble in organic solvents [7][8][9]. One the other hand, the formation of intra-and intermolecular charge transfer complex (CTC) between the electron-donating diamine and the electron-accepting dianhydride moieties explains the coloration ranging from pale yellow to deep brown, causing strong absorption in the visible region [10,11], and enhance the dielectric constant.…”
Section: Introductionmentioning
confidence: 99%